Humanization of professional preparation of specialists of agricultural sphere - POLOZENKO, Oksana (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2014)
In the article the results of the analysis of conducting of agricultural reform in Ukraine are presented, the state of agricultural sphere is described; the need of Ukraine in specialists of this sphere is defined concretely. It was grounded that preparation of specialists capable to ensure competitive carrying out of agriculture, it is necessary to fulfill taking into account the tendencies of humanization of education space